2016
DOI: 10.1016/j.jagp.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Risk of Postoperative Delirium

Abstract: Objective Previous studies have shown that elevated depressive symptoms are associated with increased risk of postoperative delirium. However, to our knowledge, no previous studies have examined whether different components of depression are differentially predictive of postoperative delirium. Methods One thousand twenty patients were screened for postoperative delirium (n = 1020) using the Confusion Assessment Method as well as through retrospective chart review. Patients underwent cognitive, psychosocial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 28 publications
2
24
3
Order By: Relevance
“…27 Smith et al found that preoperative depression was associated with increased risk of POD in patients after noncardiac surgery. 42 In the present study, neither the HADS anxiety nor the HADS depression subscale was associated with POD. It is possible that the 17 patients who declined to participate were more distressed than the other patients who participated.…”
Section: Discussioncontrasting
confidence: 72%
“…27 Smith et al found that preoperative depression was associated with increased risk of POD in patients after noncardiac surgery. 42 In the present study, neither the HADS anxiety nor the HADS depression subscale was associated with POD. It is possible that the 17 patients who declined to participate were more distressed than the other patients who participated.…”
Section: Discussioncontrasting
confidence: 72%
“…Thus, we should be aware that patients with Type D personalities may experience delirium and brain dysfunction after cardiac surgery and should be monitored carefully for depressive symptoms. Depressive symptoms are a solid predictive factor for delirium [48]; however, there is no knowledge of the association between Type D personality and depressive symptoms for prolonged acute brain dysfunction. We assume that Type D personality patients might underreport their symptoms even if they are in such an at-risk population for depression.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of peripheral inflammation reported depression-like behavior, and attributed the phenomenon to a high turnover rate of brain serotonin as a result of an exaggerated elevation in inflammatory mediators in the brain [66,67]. On the contrary, depression was not shown to occur after surgery in humans [8,68,69], but it is considered to be a risk factor for POCD [47] and postoperative delirium [70,71].…”
Section: Discussionmentioning
confidence: 99%